A Model-Driven Decision Support System for Aid in a Natural Disaster - Sepulveda-Salas, J; Bull-Torres, J (Springer Verlag, 2020)
This article deals with the architecture of a support system for helping decision makers in optimizing aid distribution during natural disaster situations. In such type of events, one of the critical tasks is the transportation of staff, people, food and medicines. Given the complexity of the operations scheduling, the article proposes a model-driven decision support system with an embedded module for solving a vehicle routing problem. © Springer Nature Switzerland AG 2020.
Keywords: Natural disasters logistics; Decision support systems; Routing